ENGINE EXHAUST PARTICULATE AND GAS PHASE CONTRIBUTIONS TO VASCULAR TOXICITY - Campen, Matthew (2014)
Cardiovascular health effects of near-roadway pollution appear more substantial than other sources of air pollution. The underlying cause of this phenomenon may simply be concentration-related, but the possibility remains that gases and particulate matter (PM) may physically interact and further enhance systemic vascular toxicity. To test this, we utilized a common hypercholesterolemic mouse model (Apolipoprotein E-null) exposed to mixed vehicular emissions (MVE; combined gasoline and diesel exhausts) for 6 h/d × 50 days, with additional permutations of removing PM by filtration and also removing gaseous species from PM by denudation. Several vascular bioassays, including matrix metalloproteinase 9 (MMP9) protein, 3-nitrotyrosine, and plasma-induced vasodilatory impairments, highlighted that the whole emissions, containing both particulate and gaseous components, was collectively more potent than MVE-derived PM or gas mixtures, alone. Thus, we conclude that inhalation of fresh whole emissions induce greater systemic vascular toxicity than either the particulate or gas phase alone. These findings lend credence to the hypothesis that the near-roadway environment may have a more focused public health impact due to gas-particle interactions.